Defective DNA polymerase beta invoke a cytosolic DNA mediated inflammatory response - Zhao, Shengyuan; Goewey Ruiz, Julia A.; Sebastian, Manu; Kidane, Dawit (Frontiers in Immunology, 2022)
Base excision repair (BER) has evolved to maintain the genomic integrity of DNA following endogenous and exogenous agent induced DNA base damage. In contrast, aberrant BER induces genomic instability, promotes malignant transformation and can even trigger cancer development. Previously, we have shown that deoxyribo-5′-phosphate (dRP) lyase deficient DNA polymerase beta (POLB) causes replication associated genomic instability and sensitivity to both endogenous and exogenous DNA damaging agents. Specifically, it has been established that this loss of dRP lyase function promotes inflammation associated gastric cancer. However, the way that aberrant POLB impacts the immune signaling and inflammatory responses is still unknown. Here we show that a dRP lyase deficient variant of POLB (Leu22Pro, or L22P) increases mitotic dysfunction associated genomic instability, which eventually leads to a cytosolic DNA mediated inflammatory response. Furthermore, poly(ADP-ribose) polymerase 1 inhibition exacerbates chromosomal instability and enhances the cytosolic DNA mediated inflammatory response. Our results suggest that POLB plays a significant role in modulating inflammatory signaling, and they provide a mechanistic basis for future potential cancer immunotherapies.